Isolasi dan Identifikasi Bakteri Halofilik Ikan Talang (Chorinemus sp.) dari Aia Bangih Pasaman Barat - Mades Fifendy; Faradilla Rattriana; Irdawati Irdawati (Bioscience, 2017)
Halophilic bacteria is microorganism that live in high salinity environments up to 30%. The bacteria can be found in foods preserved by salting like salted fish. Salted fish is preserved foods are processed by salting and drying. The bacteria that live and ruin salted fish are halophilic bacteria and heterotoleran bacteria like halobacterium, micrococcus, bacillus, pediococcus, peseudomonas and vibrio. This observation aims to determine type of halophilic bacteria found in talang fish.  This is descriptif observation held january up to february 2015 is microbiology laboratory FMIPA UNP and balai veteriner laboratory Bukittinggi. Research methods is cup statterplot methods. Sample is talang fis from Aia Bangih, west pasaman. Based on observation found isolate halophilic bacteria. Its belong to gram positve like coccus. From both, the isolates not capable produce endosopra. Talang fish from Aia Bangih, west pasaman contain two isolate halophilic bacteria consist of a genus and two species.Keywords : talang salted fish, halphilic bacteria, biochemical test